A CRITICAL ANALYSIS OF THE LEGAL AND INSTITUTIONAL FRAMEWORKS FOR THE REALISATION OF THE RIGHTS OF PERSONS WITH DISABILITIES IN ZIMBABWE (African Disability Rights Yearbook, 2021)
Zimbabwe still has a long way to go with regard to full and effective realisation of the rights of persons with disabilities (PWDs) who have endured marginalisation for a long time. This article examines Zimbabwe’s legal and institutional frameworks for the realisation of the rights of PWDs. It is an appraisal of Zimbabwe’s laws and institutions for protecting disability rights in the light of the provisions of the United Nations Convention on the Rights of Persons with Disabilities (the CRPD). With the exception of the Constitution, laws that address disability in Zimbabwe predate the CRPD and are framed along the outdated medical model. State institutions tasked with the promotion and protection of PWDs’ rights take disability issues as charity issues. The institutions have also not fared well in the past years with regard to the obligation to address marginalisation of PWDs. The time is opportune for Zimbabwe to embrace a human rights-based approach to disability. Equally, it is also an opportune time for Zimbabwe to assume the obligations towards PWDs under the CRPD by becoming a party thereto.
Keywords: Zimbabwe; rights of persons with disabilities; legal and institutional frameworks for PWDs; Rights of Persons with Disabilities; United Nations Convention